Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized for You

we will pick new questions that match your level based on your Timer History

Track Your Progress

every week, we’ll send you an estimated GMAT score based on your performance

Practice Pays

we will pick new questions that match your level based on your Timer History

Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.

It appears that you are browsing the GMAT Club forum unregistered!

Signing up is free, quick, and confidential.
Join other 500,000 members and get the full benefits of GMAT Club

Registration gives you:

Tests

Take 11 tests and quizzes from GMAT Club and leading GMAT prep companies such as Manhattan GMAT,
Knewton, and others. All are free for GMAT Club members.

Applicant Stats

View detailed applicant stats such as GPA, GMAT score, work experience, location, application
status, and more

Books/Downloads

Download thousands of study notes,
question collections, GMAT Club’s
Grammar and Math books.
All are free!

Thank you for using the timer!
We noticed you are actually not timing your practice. Click the START button first next time you use the timer.
There are many benefits to timing your practice, including:

Is \(st = t\)? --> is \(s=1\) or \(t=0\) (or both)?

(1) s = st --> \(s=0\) or \(t=1\) (or both). Not sufficient.

(2) t = ts. Directly answers the question. Sufficient.

Answer: B.

Hi Bunuel,

from st (1) : we know that 's' not equals 1 or 't' not equals 0 or both , so is this st not sufficient alone.

Pls clarify

Consider this: If \(s=0\) and \(t\neq{0}\) (\(s = st\)), then \(st\neq{t}\). Or if \(t=1\) and \(s\neq{1}\) (\(s = st\)), then \(st\neq{t}\). So, for these cases the answer to the question is NO.

If \(s=t=0\) (\(s = st\)), then \(st={t}\). Or if \(s=t=1\) (\(s = st\)), then \(st={t}\). So, for these cases the answer to the question is YES.

Consider this: If \(s=0\) and \(t\neq{0}\) (\(s = st\)), then \(st\neq{t}\). Or if \(t=1\) and \(s\neq{1}\) (\(s = st\)), then \(st\neq{t}\). So, for these cases the answer to the question is NO.

If \(s=t=0\) (\(s = st\)), then \(st={t}\). Or if \(s=t=1\) (\(s = st\)), then \(st={t}\). So, for these cases the answer to the question is YES.

Does this make sense?

Yes Bunuel, when we consider values it makes sense. But I am unable to get to this directly with out plugging values.
_________________

_________________________________ Consider Kudos if helpful

Is \(st = t\)? --> is \(s=1\) or \(t=0\) (or both)?

(1) s = st --> \(s=0\) or \(t=1\) (or both). Not sufficient.

(2) t = ts. Directly answers the question. Sufficient.

Answer: B.

@bunnel If we have a statement that restates the question , then it becomes insufficient as we don't have any additional information to answer the question. But here the equality nullifies it and directly answers the question. Hence it is sufficient. IS this reasoning correct ? i

Is \(st = t\)? --> is \(s=1\) or \(t=0\) (or both)?

(1) s = st --> \(s=0\) or \(t=1\) (or both). Not sufficient.

(2) t = ts. Directly answers the question. Sufficient.

Answer: B.

@bunnel If we have a statement that restates the question , then it becomes insufficient as we don't have any additional information to answer the question. But here the equality nullifies it and directly answers the question. Hence it is sufficient. IS this reasoning correct ? i

Not sure I can follow you.

Say the question asks: is x = 1? And (1) says that x = 1. In this case (1) is sufficient as it directly answers the question: YES x does equal to 1. This is EXACTLY the case we have with the above question.
_________________

Is \(st = t\)? --> is \(s=1\) or \(t=0\) (or both)?

(1) s = st --> \(s=0\) or \(t=1\) (or both). Not sufficient.

(2) t = ts. Directly answers the question. Sufficient.

Answer: B.

@bunnel If we have a statement that restates the question , then it becomes insufficient as we don't have any additional information to answer the question. But here the equality nullifies it and directly answers the question. Hence it is sufficient. IS this reasoning correct ? i

Not sure I can follow you.

Say the question asks: is x = 1? And (1) says that x = 1. In this case (1) is sufficient as it directly answers the question: YES x does equal to 1. This is EXACTLY the case we have with the above question.

Its about the difference between a tautological statement and this question. Reference question : https://gmatclub.com/forum/in-the-diagr ... 94414.html In the explanation you explained " This statement repeats information in the prompt, and contains no new information, so it doesn’t help us at all to figure out anything else. This statement, alone and by itself, is not sufficient." Here B is also reintroducing the information in question. what's the difference ?

@bunnel If we have a statement that restates the question , then it becomes insufficient as we don't have any additional information to answer the question. But here the equality nullifies it and directly answers the question. Hence it is sufficient. IS this reasoning correct ? i

Not sure I can follow you.

Say the question asks: is x = 1? And (1) says that x = 1. In this case (1) is sufficient as it directly answers the question: YES x does equal to 1. This is EXACTLY the case we have with the above question.

Its about the difference between a tautological statement and this question. Reference question : https://gmatclub.com/forum/in-the-diagr ... 94414.html In the explanation you explained " This statement repeats information in the prompt, and contains no new information, so it doesn’t help us at all to figure out anything else. This statement, alone and by itself, is not sufficient." Here B is also reintroducing the information in question. what's the difference ?

In the question you quote one of the statements says something that is generally true, so it adds not new info. It says something like x = x, that is generally true.

Here the question asks is \(st = t\)? (2) says t = ts. So, it gives an YES answer to the question.
_________________